2004
DOI: 10.1021/ef0499372
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polarity-Based Asphaltene Subfractions

Abstract: Structural and compositional characterization of asphaltenes that were extracted from unstable crude oils, stable crude oils, and organic solid deposits was performed to elucidate their similarities and differences. A fractionation technique that divided the asphaltenes into different subfractions, based on polarity, was used to characterize these asphaltene samples. The parameters affecting the stability of these asphaltene subfractions were elucidated. The asphaltenes that were extracted from unstable crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 24 publications
5
101
0
Order By: Relevance
“…In fact, they showed that high-polarity fractions have a great tendency to aggregate and are more difficult to remediate. 105 Continental asphaltenes are more polar than archipelago asphaltenes and are expected to aggregate more in toluene than archipelago structures. Thus, the heaviest asphaltene aggregates are thought to belong to the continental model.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, they showed that high-polarity fractions have a great tendency to aggregate and are more difficult to remediate. 105 Continental asphaltenes are more polar than archipelago asphaltenes and are expected to aggregate more in toluene than archipelago structures. Thus, the heaviest asphaltene aggregates are thought to belong to the continental model.…”
Section: Resultsmentioning
confidence: 99%
“…Both resin and asphaltene affected the polarity, the association between intramolecular and intermolecular were important even at low concentrations. The forces produced aromatic plane structures in the molecular units of resin and asphaltene which were stronger than the selfpolymerized associated asphaltene due to intermolecular forces [23]. Hence, in the association of emulsified asphalt stability and contents of asphalt four components the sum of resin and asphaltene contents was associated with the stability of grey entropy.…”
Section: The Gray Entropy Correlation Between the Stability Of Emulsimentioning
confidence: 98%
“…Results obtained by other authors have previously shown that the solubility of asphaltenes was mainly related to either the aromaticity and aliphaticity factors or polarity of asphaltenes [15][16][17][18][19][20][21].…”
Section: Separation By Flocculationmentioning
confidence: 99%